Suppressive Effect of Juzentaihoto on Vascularization Induced by B16 Melanoma Cells In Vitro and In Vivo - Ishikawa, Shintaro (Hindawi Publishing Corporation, 2012)

(untitled)
Juzentaihoto (JTT) is well known to be one of Japanese herbal medicines, and used for the supplemental therapy of cancer patients with remarkable success. The present study, therefore, was undertaken to examine the possible therapeutic mechanisms of JTT on cancer using B16 melanoma cell (B16 cell)/experimental mouse system. JTT was well mixed with rodent chow at 3.0% concentrations, and was administered orally ad libitum. Administration of JTT was started one week before tumor cell injection and continued throughout the experiment. Administration of JTT into mice significantly inhibited tumor metastasis in lungs after intravenous injection of 2 × 10(5) B16 cells in a volume of 50 μL. JTT also significantly suppressed enlargement of tumor size in hind footpad after the subcutaneous injection of 2 × 10(5) (50 μL) B16 cells. In the second part of experiments, the chamber that containing B16 cells was buried in the murine back. In JTT administrated group, vascular endothelial growth factor (VEGF) of chamber internal fluid significantly decreased, and vascularization of chamber circumference was also inhibited. These results strongly suggest that oral administration of JTT caused decrease in the generation of VEGF, which is responsible for vascularization, and results in inhibition of B16 cell metastasis.